Book Review on Sirassekadi Vidhi - Aswathi, C K; Jigeesh, P P (International Research Journal of Ayurveda & Yoga, 2022)
The book sirassekadi vidhi is one of the ancient books on treatment procedures of Ayurveda written by Puthiyedath Raman Menon, who was born in 1877 and passed away in 1965. The book attempts to authentically document the practicality of certain therapies that are very popular in Kerala but not described in any of Samhita. The reputed and mostly accepted five types of Keraliya kriyakrama viz Takradhara, Pizhichil (Kayaseka), Pindasweda, Annalepa and Thalapothichil(Sirolepa) have been explained here. In light of the basic theories of Ayurveda, their explanation and scientific analysis of their applications are carried out here from the author’s personal observation and experiences. The author has also written a Sanskrit